Adverse Events Associated With PCSK9 Inhibitors: A Real‐World Experience. Issue 2 (7th September 2018) - Gürgöze, Muhammed T.; Muller‐Hansma, Annemarie H.G.; Schreuder, Michelle M.; Galema‐Boers, Annette M.H.; Boersma, Eric; Roeters van Lennep, Jeanine E.
Abstract : In randomized clinical trials (RCTs) proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitors showed a favorable safety profile, however, "real‐world" data on adverse events (AEs) is scarce. Three datasets, a hospital registry ( n = 164), and two Pharmacovigilance databases, Lareb ( n = 149) and VigiLyze ( n = 15, 554), reporting AEs attributed to PCSK9 inhibitors (alirocumab or evolocumab) prescribed in clinical practice were analyzed. In the hospital registry, 41.5% of the patients reported any AE, most often injection‐site reactions (33.8%) and influenza‐like illness (27.9%). Twelve patients (7%) discontinued PCSK9 inhibitor treatment. Most common AE reported in the Lareb and VigiLyze database was myalgia (12.8% and 8.3%, respectively). No clinically relevant differences in gender or between drugs were observed. No specific subgroup of patients could be identified at risk of developing AEs. During follow‐up, AEs resolved in most patients (71.1%). In a real‐world setting, PCSK9 inhibitors are well tolerated with an overall safety profile comparable to RCTs.